Integrative effects of morphology, silicification, and light on diatom vertical movements - Petrucciani, Alessandra; Moretti, Paolo; Ortore, Maria Grazia; Norici, Alessandra (Frontiers in Plant Science, 2023)
Diatoms represent the most abundant and diversified class of primary producers in present oceans; their distinctive trait is the ability to incorporate silicic acid in a silica outer shell called frustule. Numerous adaptative functions are ascribed to frustules, including the control of vertical movements through the water column; this indirectly determines cell access to fundamental resources such as light and nutrients, and favours diatom escape from predators. At the same time, light guides phototroph movements in the water column by affecting cell density (e.g. by modulating Si deposition in diatoms, vacuole volume and/or solution). It was investigated how the tremendous diversity in morphology and silicification that characterizes the frustule and the crucial role of light in diatom spatial distribution govern diatom sinking capacity. To test their integrative effect, we acclimated four diatoms distinguished by frustule traits (Chaetoceros muelleri, Conticribra weissflogii, Phaeodactylum tricornutum, Cylindrotheca fusiformis) to different light conditions and evaluated their physiological performance in terms of growth, elemental composition, morphological changes, as well as their in vivo sinking capacity. What emerged from this study was that silicification, more than other morphological characteristics, controls species vertical movements, while a higher energy availability enhances cell floating independently from the silica content.